Digital Transformation in the Workplace: A Bibliometric Exploration of Co-Occurrence Networks and Emerging Themes in Scholarly Literature - Mishra, Sanjib (International Journal of Humanities, Education, and Social Sciences, 2025)
Background: The COVID-19 pandemic accelerated digital workplace transformation, sparking global research into its socio-technical and human-centric impacts. This study maps scholarly trends to uncover key themes and gaps. Methods: A bibliometric analysis of 133 Scopus-indexed Social Sciences articles (open-access, 2012–2025) was conducted using VOSviewer. Keywords digital, workplace, and experience guided data extraction, with co-occurrence networks and bibliographic coupling identifying thematic clusters. Results: Post-2020, publications surged (peaking at 31 in 2023), driven by remote work and AI integration. Thematic clusters highlighted pandemic-driven pedagogy, workplace well-being, gig economy exploitation, and blurred work-life boundaries. The UK and Australia led research output, while Progress in Human Geography and BMC Medical Education anchored high-impact contributions. Keywords like “Covid-19,” “digitization,” and “gender” underscored tensions between efficiency and equity. Conclusion: Digital workplace research remains fragmented, dominated by Anglophone perspectives and theoretical silos. Future work must prioritize equitable policies, cross-cultural collaboration, and ethical frameworks to balance technological advancement with human well-being.